2017
DOI: 10.1002/chem.201702360
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Design of Bicontinuous Gyroid Mesoporous Carbon and Nitrogen‐Doped Carbon from Poly(ethylene oxide‐b‐caprolactone) Diblock Copolymers

Abstract: Highly ordered mesoporous resol-type phenolic resin and the corresponding mesoporous carbon materials were synthesized by using poly(ethylene oxide-b-caprolactone) (PEO-b-PCL) diblock copolymer as a soft template. The self-assembled mesoporous phenolic resin was found to form only in a specific resol concentration range of 40-70 wt % due to an intriguing balance of hydrogen-bonding interactions in the resol/PEO-b-PCL mixtures. Furthermore, morphological transitions of the mesostructures from disordered to gyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…In a soft template synthesis strategy, the templates are usually organic molecules or supermolecules with functional groups 84,121. In the particular solvent, the functional groups of soft templates can provide strong interaction force, such as hydrogen bonding,137,138 hydrophilic and hydrophobic interactions,139,140 or electrostatic interactions 141,142. Once the proper solvent is added, the soft templates turn into micelles.…”
Section: Template Methodsmentioning
confidence: 99%
“…In a soft template synthesis strategy, the templates are usually organic molecules or supermolecules with functional groups 84,121. In the particular solvent, the functional groups of soft templates can provide strong interaction force, such as hydrogen bonding,137,138 hydrophilic and hydrophobic interactions,139,140 or electrostatic interactions 141,142. Once the proper solvent is added, the soft templates turn into micelles.…”
Section: Template Methodsmentioning
confidence: 99%
“…To fabricate the mesoporous carbons, we first synthesized an amphiphilic PEO-PCL block copolymer with specific molecular weightf ractions( EO 114 -CL 92 )a st he template;i np revious studies, we found that such templates are suitable for the preparation of ordered mesoporousc arbonsw ith hexagonal cylinder and gyroid structures. [26][27][28][29] The resol-type phenolic resin and this PEO-PCL template were dissolved in EtOH at as pecific weightr atio;t he microphase transferredg radually to an ordered structurea fter evaporation-induced self-assembly and curing in the oven, with the electrode materials for EDLCs upercapacitors obtained after carbonization and activation processes (Scheme 1). The weightr atios of resol to PEO-PCLc ould be regulated during the fabrication of the mesoporousc ar-bons to induce differentt ypes of microphase separation, based on the corresponding volume fractionso ft he PCL and resol/PEOd omains.…”
Section: Resultsmentioning
confidence: 99%
“…[31] The resol was prepared through condensation of phenol, CH 2 Ow ith NaOH, producing ar esol resin with an average molecular weight (M n )o fapproximately 500. [26]…”
Section: Peo-pcla Nd Resol-type Phenolic Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the soft-templating method is a straightforward approach which is dependent on the self-assembly of the organic compounds and block copolymers into ordered mesostructured composites in a oriented manner through a chemical interaction. [9][10][11][12][13] Interestingly, the morphology, porosity, and structure could be tuned by controlling the synthetic conditions, such as the concentration of the surfactant, pH, and carbonization temperature. The morphological control will endow the product with an excellent chemical activity, mechanical stability, good electrical conductivity, and high surface area, which have been considered as the essential requirements for electrode materials used in energy storage applications.…”
Section: Introductionmentioning
confidence: 99%